Importance of high crude fibre insect frass for effective alleviation of ammonium (NH4 + ) toxicity and optimal growth of the short-term vegetable, amaranthus tricolor - Dahlia Shahbuddin; Ansaruddin Othman; Ahmad Bukhary Ahmad Khair (Universiti Kebangsaan Malaysia, 2023)
This study focused on the efficacy of the fecal matter component from insect-derived frass containing high total crude fibre (TCF) for the effective alleviation of ammonium (NH4 +) toxicity in short-term vegetables. Two types of insect-derived frass, bred from different feeding substrates, the black soldier fly (BSF) larvae, Hermetia illucens, known as the BSF frass (BSFF), and the common house cricket (CHC), Acheta domesticus, of both adults and nymphal instars, known as CHC frass (CHCF). The short-term vegetable, Amaranthus tricolor, was chosen as the test crop. A total of 200 A. tricolor vegetable seedlings were tested, with five experimental replicates, each with 10 A. tricolor seedlings set following completely randomized design, each for the different fertilizer treatments, BSFF fertilizer, CHCF fertilizer, NPK 15:15:15 fertilizer as the positive control, and no fertilizer as the negative control, pre-prepared in the form of soil–fertilizer mixtures, applied following the rate of 120 kg N ha−1. Comparatively, BSFF fecal matter component recorded lower rates of decomposition of total organic matter (TOM), total organic carbon (TOC), and organic nitrogen (ON) but with a higher rate of TCF decomposition, contrary to CHCF with higher rates of decomposition of TOM, TOC, ON, and a lower rate of TCF decomposition. Additionally, the rates of ON decomposition to NH4 + and NH4 + uptake were lower for BSFF compared to CHCF. The ratio rates of TOM-TCF (22:31), TOM-ON (22:02), TOC-TCF (30:31), and TOC-ON (30:02) for BSFF recorded the highest difference, compared to CHCF with a lower difference of ratio rates; TOM-TCF (36:21), TOM-ON (36:13), TOC-TCF (38:21), and TOC-ON (38:13). The alleviation of NH4 + toxicity for short-term vegetables with high sensitivity toward excessive NH4 + uptake could only be effectively alleviated with high TCF fecal matter component of the frass, increasing decomposition toward the TCF element and reduced decomposition on the organic N element of the frass’ fecal matter.